2022
DOI: 10.1038/s41598-022-04862-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of hyperuricemia for patients with sepsis in the intensive care unit

Abstract: This study evaluated the relationship between hyperuricemia at admission and the clinical prognosis of patients with sepsis. The data were obtained from the Intensive Care Medical Information Database III. The patients were divided into a normal serum uric acid group and a hyperuricemia group. The main outcome was 90-day mortality, and the secondary outcomes were hospital mortality, 30-day mortality, and acute kidney injury. Propensity score matching was used to balance the baseline characteristics of the grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
11
0
2
Order By: Relevance
“…Interestingly, hyperuricemia contributed to the elevation of fatality risk in non-neonatal listeriosis. Previous reports revealed that hyperuricemia was associated with increased risk of 90-day all-cause mortality and the incidence of acute kidney injury in patients with sepsis [ 48 ]. High uric acid levels were also associated with adverse outcomes in patients hospitalized for coronavirus disease 2019 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, hyperuricemia contributed to the elevation of fatality risk in non-neonatal listeriosis. Previous reports revealed that hyperuricemia was associated with increased risk of 90-day all-cause mortality and the incidence of acute kidney injury in patients with sepsis [ 48 ]. High uric acid levels were also associated with adverse outcomes in patients hospitalized for coronavirus disease 2019 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the papers that have been reported have produced conflicting results. Many reports that hyperuricemia is associated with sepsis [ 43 , 44 , 45 , 46 ], sepsis-induced ARDS [ 47 ], AKI prognosis [ 48 ], prolonged hospital stay [ 43 ], or that uric acid increases over time [ 49 ]. On the contrary, some reports suggest that hypouricemia may be a poor prognostic factor for sepsis or sepsis-associated ARDS [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are similar relationships between serum UA levels and infectious diseases. The study by Liu et al in 954 ICU patients with sepsis showed that high UA level was associated with mortality (HR: 1.65) and AKI (HR:1.77) (15). In a study conducted on ICU patients with sepsis, UA levels were higher in patients with acute respiratory distress syndrome (ARDS) and who died.…”
Section: Mid Blac Sea J Health Scimentioning
confidence: 99%